Chapter 11 Análisis numérico de la reparación y refuerzo de estructuras con FRP - Nallim, Liz (OmniaScience, 2014)
This chapter presents a procedure to assess the magnitude of the damage local and global damage in structures subjected to static and dynamic actions, with special emphasis on the seismic problem. In addition to the formulation for the evaluation of the damage, introduces the concept of structural reinforcement and repair by composite laminates of epoxy matrix with carbon fiber reinforcement. For this purpose, the use of the theory of mixtures to compose a composite material from their basic components. Damage is also assessed in these reinforced and / or repaired structures and the influence of these improvements on the assessment of the overall damage of the structure is discussed.